An autopsy-based evaluation of deaths of homeless unknown persons (HUPs). Issue 1 (2nd January 2017) - Chaudhary, B. L.; Vidua, Raghvendra Kumar; Pramanik, Parthasarathi; Kumar, Arvind; Singh, Sukhdeep
ABSTRACT: Background: India is a significant host to homeless unknown persons (HUPs) and subsequently to their untimely deaths due to various reasons. The autopsy-based evaluation has been always important in knowing the exact reasons behind it. Objective: To know about the epidemiological mortality profile such as magnitude, cause and manner of death, seasonality, and year-wise distribution of their untimely and unattended deaths. Materials and Methods: A retrospective autopsy-based evaluation of unnatural deaths among HUPs was done at LHMC, New Delhi for a total duration of 5 years (January 2006 to December 2010). Results: Out of 749 cases in the study group in this duration, 536 deaths have been caused due to some natural events and 213 due to some unnatural events. Among the natural deaths, the pulmonary pathology did contribute for 509 cases. Conclusion: The study population is a vulnerable segment of the society which often suffers the extreme adversity of natural and unnatural events in the form of their deaths. It is a significant host to the pulmonary infections that often spread to the other segments of the society at the point of contact. Thereby it deserves an urgent public health intervention and a policy response for the same for the well-being of HUPs and the general public at large.